Pengetahuan Masyarakat Berhubungan dengan Kepatuhan dalam Penerapan 3M Pencegahan Covid-19 : Public Knowledge Related to Compliance in the Implementation of 3M Covid-19 Prevention - Kumalasari, Tyas; Riyadi, Muskhab Eko; Yulina Amry, Riza (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2022)
The health problem that is currently receiving global attention is the Covid-19 disease. Coronavirus disease first appeared in December 2019 in Wuhan City, China. The United States was still the country with the most cases, namely 3,896,855 cases of coronavirus infection, and Indonesia was ranked 25. The number of cases in Indonesia was still above China and below Egypt which recorded 87,775 cases, while Bantul Regency occupies the highest case in DI Province. Yogyakarta, where the active status is 30,366. One of the most important things to pay attention to in the context of handling Covid-19 cases is knowledge, especially public knowledge which is still low in terms of preventing the transmission of the spread of the Covid-19 virus. The purpose of the study was to determine the relationship between knowledge and community compliance in the application of 3M. This study was non-experimental with a cross-sectional design. The population was the people in Potorono Village, Banguntapan, Bantul. The sampling technique used a consecutive sampling technique and obtained a large sample of 80 respondents. The statistical test used the Chi-Square test. The results showed that most of the community's knowledge was in a good category and community compliance in the application of 3M was in the obedient category. The results of the statistical test obtained a p-value of 0.000 (p<0.05), which means that there was a relationship between public knowledge and compliance in the application of 3M. Communities recommended maintaining compliance in the application of 3M.